2021
DOI: 10.1038/s41598-021-02178-2
|View full text |Cite
|
Sign up to set email alerts
|

A proximity proteomics screen in three-dimensional spheroid cultures identifies novel regulators of lumen formation

Abstract: Apical-basal cell polarity and lumen formation are essential features of many epithelial tissues, which are disrupted in diseases like cancer. Here, we describe a proteomics-based screen to identify proteins involved in lumen formation in three-dimensional spheroid cultures. We established a suspension-based culture method suitable for generating polarized cysts in sufficient quantities for proteomic analysis. Using this approach, we identified several known and unknown proteins proximally associated with PAR6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 80 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…In contrast, no obvious lumen formation was found in “all-stiffened” hydrogel, and the spheroid had denser cell organization (Figure S16b). In addition, previous studies have shown that lumen formation of MCF-7 is related to cell apoptosis due to hypoxia or autophagy. , However, it is worth noting that their spheroid size is much larger than ours (they used anchorage-independent growth protocol instead of our 3D scaffolds), and a dark area in the central region which represented “cell death region” was not observed here. To better understand the structure of the spheroid, we used DAPI to stain the cell nucleus on day 17.…”
Section: Resultsmentioning
confidence: 53%
“…In contrast, no obvious lumen formation was found in “all-stiffened” hydrogel, and the spheroid had denser cell organization (Figure S16b). In addition, previous studies have shown that lumen formation of MCF-7 is related to cell apoptosis due to hypoxia or autophagy. , However, it is worth noting that their spheroid size is much larger than ours (they used anchorage-independent growth protocol instead of our 3D scaffolds), and a dark area in the central region which represented “cell death region” was not observed here. To better understand the structure of the spheroid, we used DAPI to stain the cell nucleus on day 17.…”
Section: Resultsmentioning
confidence: 53%
“…Three-dimensional tumor models, such as spheroids, offers an improved model to assess molecular and physiological aspects that are essential for drug development including drug penetration, hypoxic/necrotic environment, stemness and cell interaction, among many others 19,20 . Traditionally, spheroid models have been technically challenging, especially from a proteomics perspective, due to the low protein amount obtained from single spheroids, which typically requires pooling of several spheroids per condition to achieve a reasonable proteome coverage [21][22][23] . These limitations are even more evident when studying the phosphoproteome layer, due to the need for phosphoenrichment prior to LC-MS/MS measurements.…”
Section: Phosphoproteomics Signature In 2d Vs 3d Model Of Colorectal ...mentioning
confidence: 99%
“…We used proximity labeling technology [ 37 ] to elucidate CLDN18.2’s mechanism in promoting the juxtacrine interaction between gastric cancer cells and CAFs. We overexpressed CLDN18.2 in gastric cancer cells with an overexpressed biotin tag, and after subcutaneous injection into a mouse tumor model, we used mass spectrometry to confirmed that CLDN18.2 may produce a series of tumor-promoting effects by interacting with S100A4 in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…We used proximity labeling technology [37] to elucidate CLDN18.2's mechanism in promoting the juxtacrine interaction between gastric cancer cells and CAFs. We The N-terminus of CLDN18.2 was coupled to HA-turboID with a linker, HA-turboID was coupled to the N-terminus of PDFGRB with a linker.…”
Section: Discussionmentioning
confidence: 99%